Alkyl Protocatechuate-Loaded Nanostructured Lipid Systems as a Treatment Strategy for Paracoccidioides brasiliensis and Paracoccidioides lutzii In Vitro - Medina-Alarcón, Kaila P.; Singulani, Junya L.; Voltan, Aline R.; Sardi, Janaina C. O.; Petrônio, Maicon S.; Santos, Mariana B.; Polaquini, Carlos R.; Regasini, Luis O.; Bolzani, Vanderlan S.; da Silva, Dulce H. S.; Chorilli, Marlus; Mendes-Giannini, Maria J. S.; et al. (Frontiers in Microbiology, 2017)
Dodecyl protocatechuate (dodecyl) is a derivative of protocatechuic acid (3,4-dihydroxybenzoic acid) that possesses anti-oxidant and antifungal properties. Nanostructured lipid systems (NLS) can potentiate the action of many antifungal agents, reducing the required dose and side effects by improving their activity. This work aimed to evaluate dodecyl protocatechuate loaded into a nanostructured lipid system (NLS+dodecyl) as a strategy for the treatment of Paracoccidioides brasiliensis and Paracoccidioides lutzii in vitro. Antifungal activity against P. brasiliensis and P. lutzii was evaluated using the microdilution technique. NLS+dodecyl showed high antifungal activity with a minimum inhibitory concentration (MIC) ranging from 0.06 to 0.03 μg/mL; 4 to 16-fold higher than that of free dodecyl. NLS+dodecyl was able to inhibit fungal adhesion of the extracellular artificial matrix proteins (laminin and fibronectin), resulting in 82.4% and 81% inhibition, respectively, an increase of 8% to 17% compared with free dodecyl. These findings corroborate previous results demonstrating 65% and 74% inhibition of fungal adhesion in pulmonary fibroblast cells by dodecyl and NLS+dodecyl, respectively, representing a 9% increase in inhibition for NLS+dodecyl. Subsequently, cytotoxicity was evaluated using the 0.4% sulforhodamine B assay. NLS+dodecyl did not exhibit cytotoxicity in MRC5 (human pneumocyte) and HepG2 (human hepatic carcinoma) cells, thus increasing the selectivity index (SI) for NLS+dodecyl. In addition, cytotoxicity was evaluated in vivo using the Caenorhabditis elegans model; neither dodecyl nor NLS+dodecyl exhibited any cytotoxic effects. Taken together, these results suggest that NLS can be used as a strategy to improve the activity of dodecyl against P. brasiliensis and P. lutzii because it improves antifungal activity, increases the inhibition of fungal adhesion in lung cells and the extracellular matrix in vitro, and does not exhibit any toxicity both in vitro and in vivo.